DETERMINATION OF GENETIC DIVERSITY IN THE VICIA L. (SECTION VICIA) BY USING SDS-PAGE - Emre, Irfan (Pakistan Botanical Soc, 2011)
The interspecific and intraspecific variations in some taxa of Vicia is explained by SDS-PAGE method. In this study, nine Vicia L. Taxa, collected from different regions of Turkey have been studied for the analysis of seed storage protein profiles to examine their relationship. The differences among species were observed and all nine taxa were clearly identifiable from the protein patterns. Electrophoretic data were documented by using a gel documentation system (Bio-Rad, USA) and analysed by using Quantity 1-D analysis software and a dendogram has constructed with 4.0 % tolerance in UPGAMA (Unweighed Pair-Group Arithmetic Mean). The dendogram from SDS-PAGE analysis showed that all studied taxa constituted two clusters. The first one consisted of V. noeana var. noeana, V. noeana var. megalodonta, V. truncatula, V. peregrina, V. michauxii and V. grandiflora second one by V. mollis, V. hybrida, and V. assyriaca. Present results showed that all studied species have similar total protein content. But V. truncatula (86.837 mu g/ml) and V. hybrida (83.209 mu g/ml) have highest total protein content. Whereas V. grandiflora (65.860 mu g/ml) has low total protein content.
Keywords: Rapd-Pcr; Seed; Fabaceae; Peregrinae; Hypechusa; Isozymes; Proteins; Patterns